Non-alcoholic fatty liver disease - Li, Wenhao (Clin Med (Lond), 2020)
Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease worldwide. NAFLD is defined by excess fat in the liver and has a multidirectional relationship with metabolic syndrome. The prevalence of NAFLD has risen rapidly in recent years in line with the obesity epidemic and associated increases in type 2 diabetes, hypertension and hypercholesterolaemia. Patients with NAFLD are at risk of cardiovascular disease and cancer, and in a proportion of individuals, NAFLD is associated with liver damage. This article summarises the epidemiology of NAFLD, the clinical approach to risk-assessing patients and briefly outlines current and future management options.